Estimate levels of some cytokine in patient infection with Helicobacter pylori (Journal of the College of Basic Education, 2022)
This study includes a collection of 140 samples of blood which have been collected from patient infected with H. pylori ,these samples were collected from AL – Kindy Teaching Hospital in a period from ( November- 2015 to March - 2016 ) with age ranging from 15- 70 years . The results showed that from 140 blood samples diagnosis infection with H.pylori by rapid test and make confirmatory for the infection by ELISA technique, make ELISA IgG test technique in this test give 60 patients. Measure the serum level cytokine in the patient infected with H.pylori explain that anti-inflammatory IL-6 chronic phase: (391±5.4 pg/ml )and acute phase : (218.6±7.7 pg/ml) . In the cytokine pro inflammatory TNF-α chronic phase : (391.8±8.6 pg/ml) and acute phase :(290±11.3 pg/ml) and in the proinflammatory MIF cytokine chronic phase : (45.05±2.5 pg/ml) and acute phase : (29.08±2.1 pg/ml) .